The Use of Kahoot Media in Arabic Language Learning to Improve Students' Ability to Understand Reading Texts - Wilda Nur Solihat; Agus Gunawan; Obby Syukri Mahdiyin; Rijaludin Iqbal Fauzi (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
This study aims to determine the effectiveness of Kahoot media in Arabic language instruction in improving students' reading skills. It employed a quasi-experimental method with a pre-test and post-test design involving a single experimental group. The participants were seventh-grade students at SMP Al-Azhar Cairo Bandung. The primary focus of this study was to compare students' reading abilities before and after the implementation of the interactive media Kahoot and to evaluate whether it was more effective than traditional teaching methods. The results indicated that students' reading skills before using Kahoot were relatively low, with an average score of 50.8, which falls into the 50–59 category based on interpretation criteria. After the implementation of Kahoot, a significant improvement was observed, with the average score rising to 82.4, classified as "good" (80–90). And 65% of students reached a reading proficiency level considered moderate. A hypothesis test revealed that the calculated t-value (25.32) was greater than the critical t-value (2.06), indicating that the improvement was statistically significant. These findings demonstrate that Kahoot effectively enhances students' reading skills in Arabic. Future research is encouraged to explore the impact of Kahoot on other Arabic language skills, such as listening, speaking, and writing, as well as to assess its long-term effectiveness across different educational levels.